Arguments in Syntax and Semantics - Williams, Alexander (Cambridge : Cambridge University Press, 2015)
Argument structure - the pattern of underlying relations between a predicate and its dependents - is at the base of syntactic theory and the theory of the interface with semantics. This comprehensive guide explores the motives for thematic and event-structural decomposition, and its relation to structure in syntax. It also discusses broad patterns in the linking of syntactic to semantic relations, and includes insightful case studies on passive and resultative constructions. Semantically explicit and syntactically impartial, with a careful, interrogative approach, Williams clarifies notions of argument within both lexicalist and nonlexicalist approaches. Ideal for students and researchers in syntactic and semantic theory, this introduction includes: A comprehensive overview of arguments in syntax and semantics Discussion questions and suggestions for further reading A glossary with helpful definitions of key terms.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Persuasion (Rhetoric)